Semiótica das culturas e os autocratas da solidão: a formação da identidade latino-americana e as estratégias de poder no romance Cem Anos de Solidão, de Gabriel García Márquez - Sobrinho Neto, José Veloso de Araújo (2023)
The research sought to investigate, in the work One hundred years of solitude (1967), by the Colombian writer Gabriel García Márquez, the relationship between the strategies of “power” (manipulation, subjection) – immanent to the enunciative choices – and the formation of the “identity” of the people Latin American. The interest in analyzing the novel stems from the polysemic richness of the plot that brings together myth and history in a plot focused on the genealogy of a family cursed by congenital loneliness. of a great metaphor, the universal, the political, economic and social conjecture of the formation of Latin America. We opted for the analytical categories of “power” and “identity” because we believe that the strategies for controlling bodies and populations had a fundamental influence on the formation of Latin American social and political features. Thus, the methodological basis used favors the theoretical foundation of the Semiotics of Cultures, developed by François Rastier, and in order to situate the analytical category of “power”, we rely on the studies of professor, sociologist and historian Michel Foucault. In the body of the work, we initially tried to demonstrate the convergence of different theoretical currents. In a second moment, appropriating this knowledge, we tried to lay bare, demonstrate, in the text's statement, the strategies of power and the symbolic networks that influenced, better, forged, the culture and identity of the Latin American people. The results obtained in the analysis of the corpus indicated that the signs – linguistic or not – have the power to mold, to regulate, to subject individuals, but also to stabilize, to control, to constrain, the internal processes (in the subject) and external ( in the people) of ruptures; but they are, in the opposite sense, the greatest threat to the established power. After all, man passes from nature to culture, from myth to history due to language, it is to be assumed that he leaves culture and history for the cataclysm and the end by her action.